2011
DOI: 10.5194/nhess-11-2137-2011
|View full text |Cite
|
Sign up to set email alerts
|

Scale orientated analysis of river width changes due to extreme flood hazards

Abstract: Abstract. This paper analyses the morphological effects of extreme floods (recurrence interval > 100 years) and examines which parameters best describe the width changes due to erosion based on 5 affected alpine gravel bed rivers in Austria. The research was based on vertical aerial photos of the rivers before and after extreme floods, hydrodynamic numerical models and cross sectional measurements supported by LiDAR data of the rivers. Average width ratios (width after/before the flood) were calculated and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 39 publications
3
70
1
2
Order By: Relevance
“…In this work, the term channel refers to an active channel, which includes low-flow channels and unvegetated or sparsely vegetated bars (i.e., exposed sediments). Channel width was calculated dividing channel area by the length of the reach or subreach, and changes in channel width were expressed as a width ratio, i.e., channel width after/channel width before the flood (Krapesch et al, 2011). Estimate of channel width, and consequently of width ratio, is affected by errors, in particular related to photo interpretation and digitization.…”
Section: Morphological Changes: Analysis Of Channel Wideningmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the term channel refers to an active channel, which includes low-flow channels and unvegetated or sparsely vegetated bars (i.e., exposed sediments). Channel width was calculated dividing channel area by the length of the reach or subreach, and changes in channel width were expressed as a width ratio, i.e., channel width after/channel width before the flood (Krapesch et al, 2011). Estimate of channel width, and consequently of width ratio, is affected by errors, in particular related to photo interpretation and digitization.…”
Section: Morphological Changes: Analysis Of Channel Wideningmentioning
confidence: 99%
“…Another major research question concerns the factors controlling channel response to a large flood event. Most works have focused mainly on hydraulic variables (e.g., unit stream power, flow duration above a critical threshold; see Magilligan, 1992;Cenderelli and Wohl, 2003;Kale, 2007;Krapesch et al, 2011;Magilligan et al, 2015) but, as suggested by Costa and O'Connor (1995), understanding and prediction of channel and floodplain response to a large flood should incorporate additional factors. Some works have confirmed that hydraulic forces may not be sufficient to explain geomorphic effects (e.g., Heritage et al, 2004;Nardi and Rinaldi, 2015), and consequently, attempts have been made to include other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking, past research has shown that geomorphic impacts from floods may be pronounced where resistance thresholds are low (Baker and Costa, 1987), energy expenditure is enhanced by local and regional controls (Nanson, 1986;Miller, 1990a), and where the timing of coarse and fine sediment inputs coincides with the peak discharge (Cenderelli and Kite, 1998;Magilligan et al, 1998). In some instances, responses may relate to significant erosion, including channel widening (Krapesch et al, 2011), floodplain stripping (Nanson, 1986) or intensified mass wasting (Miller, 1990b;Newson, 2006). In other instances, the catastrophic effects include massive overbank deposition (Knox, 1987(Knox, , 2006, the transport of channel bed gravels onto floodplains (Ritter, 1975), or the entrainment and transport of coarse bedload material (Eaton and Lapointe, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…where Q is the discharge (m 3 s −1 ), ρ is the water density (1000 kg m −3 ), g is the gravitational acceleration (m s −2 ), and W is the channel width before the evaluated flood event (m), has been often applied to calculations of bedload transport and channel response in fluvial geomorphology (Magilligan, 1992;Krapesch et al, 2011;Thorne et al, 2011;Nardi and Rinaldi, 2015). Because obtaining the input variables is easy and high-resolution digital elevation models are readily available, this parameter can be used to identify dominant processes within channels (i.e., erosion or deposition reflecting relatively higher or lower values of ω during flood events), although the sediment supply from the upstream reaches should be carefully considered (Vocal Ferencevic and Ashmore, 2012;Bizzi and Lerner, 2013).…”
Section: Introductionmentioning
confidence: 99%